English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

9 answers

2^3 = 8

|-4| = 4 so -|-4| = -4

8^2 = 64

The equation becomes (8-7)(-4+64)-3 or (1)(60)-3 = 57.

2007-01-26 06:43:20 · answer #1 · answered by uahgrad05 3 · 0 0

2^3 - 7) ( - |-4| +8^2) -3 =
(8 - 7) (-4 + 64) - 3 =
1* 60 - 3 = 57
><

2007-01-26 14:46:18 · answer #2 · answered by aeiou 7 · 0 0

2^3 =8
8^2=64

(8-7)(-4+64)-3 = 1x-60-3 = 57

2007-01-26 14:51:47 · answer #3 · answered by sm bn 6 · 0 0

(2^3 - 7)(- | -4 | + 8^2 ) - 3
(8 - 7)( - | -4 | + 64) - 3
(1)( - | -4 | + 64) - 3
(1)( -4 + 64) - 3
(1)(60) - 3
60 - 3
57

2007-01-26 14:45:29 · answer #4 · answered by SPB 6 · 0 0

57

2007-01-26 14:40:49 · answer #5 · answered by Anonymous · 0 0

(2x2x2 - 7)(-4+64)-3
(8-7)(60)-3
ok so i dont know if the -3 is minusing or division but if its division the anser is:
(1)(60)-3=180
but if its minus it = 57

2007-01-26 14:49:27 · answer #6 · answered by Hazel-Iris 2 · 0 0

(8-7) (-4 + 64) -3
(1)(60) - 3
60 - 3

57

2007-01-26 14:43:43 · answer #7 · answered by bequalming 5 · 0 0

the answer is 57. Technically though I think that you sould say solve not simplify. I don't see any variables.

2007-01-26 14:43:29 · answer #8 · answered by Annonymas 3 · 0 0

(8-7)(-4+64)-3
missing part

2007-01-26 14:51:11 · answer #9 · answered by iyiogrenci 6 · 0 0

fedest.com, questions and answers